Comparative Study on Protein Composition and Foam Characteristics of Barley and Wheat Beer - Xiu Li; Kai Jiang; Yuhong Jin; Junhan Liu (Foods)
Protein is an important component of beer, and its type, content and molecular weight directly affect the quality of beer, especially the foam quality of beer. Different brands of wheat beer and barley beer available in the market were used for this analysis. The differences in protein composition and foam performance between multi-sample barley and wheat beer were analyzed using sodium dodecyl sulfate-polyacrylamide gel electrophoresis and high-pressure size exclusion chromatography. Protein significantly influences beer quality, particularly its foam properties. Wheat beer (WB) has 9.52–84.10% more total protein content than barley beer (BB). The primary proteins in both beers are 6.9–20.1 kDa, with WB having 1.04 g/L more of this protein, 60.11% higher than that of BB. It is one of the main different proteins between WB and BB. WB also contains 66.67% more 20.1–32.4 kDa protein compared to BB. This is one of the main differences between WB and BB proteins. Both 6.9–20.1 kDa and 20.1–32.4 kDa proteins enhance beer viscosity and foam properties. Additionally, WB’s > 32.4 kDa protein content is 246.67% higher than BB’s, significantly improving beer hydrophobicity and foam performance. These protein differences are key factors in the superior foam quality of WB.